2011
DOI: 10.1080/09523987.2011.632280
|View full text |Cite
|
Sign up to set email alerts
|

Learning Spanish withLaura: the effects of a pedagogical agent

Abstract: The purpose of this study was to investigate the effects of an animated pedagogical agent on Spanish vocabulary learning. Furthermore, the study examined learners' reactions and attitudes towards the presence of the pedagogical agent in the web-based environments. A total of 47 university students enrolled in two fourth-semester Spanish classes participated in this study. The data were collected through a demographic information questionnaire, a vocabulary pretest and two vocabulary post-tests (an immediate po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…For instance, some learners reported that they were distracted by the eye and head animation of Laura, a virtual tutor that teaches Spanish [44]. Another study showed that non-task messages conveyed by a pedagogical agent distracted learners away from the main learning content [45].…”
Section: Pedagogical Agent Enthusiasm and Extraneous Cognitive Loadmentioning
confidence: 99%
“…For instance, some learners reported that they were distracted by the eye and head animation of Laura, a virtual tutor that teaches Spanish [44]. Another study showed that non-task messages conveyed by a pedagogical agent distracted learners away from the main learning content [45].…”
Section: Pedagogical Agent Enthusiasm and Extraneous Cognitive Loadmentioning
confidence: 99%
“…In addition to the generally positive results revealed in the reviewed studies, some yielded fewer positive results. For example, it was found that web-based pedagogical agent-assisted vocabulary systems could not improve learners' vocabulary recall and retention, though most learners expressed satisfaction with the learning environment (e.g., Theodoridou, 2011). In the Turkish EFL context, teachers and students both had a negative and pessimistic view towards the reliability of the AI-based assessment system, because it only evaluated the level of memory rather than assessing foreign language skills and higher order thinking skills (e.g., Ulum, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…(a) The effectiveness of AI-supported pedagogical agents in students' vocabulary learning (e.g., Theodoridou, 2011), and students' productive dialogue (e.g., Ayedoun et al, 2019;Tegos et al, 2014).…”
Section: Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are designed to support learning and instruction in interactive learning environments in which learners can interact and have meaningful conversations [20], [21]; [22]. They can be used for many purposes including advising, tutoring, coaching, demonstrating, and modeling [23], [24] and as a learning companion or peer who encourages and motivates learners to put more effort into learning [25], [26].…”
Section: The Pedagogical Agentmentioning
confidence: 99%